The Effect of Baby Massage on Defecation Frequency in Babies Aged 6-12 Months - ardhana, Pramodya; Retnaningsih, Reny (Jurnal MID-Z (MIDWIFERI ZIGOT), 2024)
Defecation is the process of removing waste products from the rectum, which are materials the body has not needed for a long time and need to be removed. In newborns, the normal change in stool frequency happens between 6 and 12 months of age; at this time, irregularities in the frequency of bowel movements are linked to malnutrition and weight loss. Bowel motions occur in babies at different rates, ranging from 8–10 times per day to 2-3 times per week. In Indonesia, up to 73.2% of kids suffer from digestive issues, specifically constipation and diarrhea. There are pharmaceutical and non-pharmacological treatments available for the treatment of gastrointestinal diseases. Non-pharmacological therapy combined with massage therapy, and pharmaceutical therapy combined with medication delivery. This study set out to find out how often infants between the ages of 6 and 12 months had bowel movements in response to massage. Pre-experimental methodology with a single group pretest-posttest design is used in this kind of study. Using purposive sampling procedures, a sample of up to 29 infants between the ages of 6 and 12 months was acquired from Federer's formula. The Wilcoxon test findings showed a p-value of 0.000, indicating that there is a relationship between infant massage and the frequency of bowel movements in newborns (p < 0.005). In conclusion, massage therapy for infants has an impact on how frequently 6 to 12-month-olds poop.